2020
DOI: 10.1088/1757-899x/896/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric dispersion modelling of dust emissions from the dried bottom of the Aral Sea

Abstract: The problem of spreading of harmful emissions from the dried part of the Aral Sea is extremely relevant for the Central Asian region, but it is also important for other countries of the near and far abroad in view of the transboundary transport of pollutants in the atmosphere. In order to solve the problem of predicting the distribution of the concentration of air pollutants, researchers are usually use mathematical tools. Modelling the processes of transport and diffusion of pollutants in the atmosphere claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Numerical modeling showed that both direct problems, when the output variables of the problem were considered unknown -the maximum temperature inside the storage facility and the duration of the period when the specified temperature level was exceeded, are correctly posed. The value of the learning error did not exceed 1% [13][14][15]. In contrast, all six inverse / combined problems turned out to be incorrect with a learning error of 25-35%.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical modeling showed that both direct problems, when the output variables of the problem were considered unknown -the maximum temperature inside the storage facility and the duration of the period when the specified temperature level was exceeded, are correctly posed. The value of the learning error did not exceed 1% [13][14][15]. In contrast, all six inverse / combined problems turned out to be incorrect with a learning error of 25-35%.…”
Section: Resultsmentioning
confidence: 99%
“…Suppose there is no pressure gradient. If the first equation from the Navier -Stokes system is differentiated concerning z, the second concerning x, then we obtain [18][19][20]:…”
Section: K If the Layer Is Underground If The Layer Is In The Atmospher Hmentioning
confidence: 99%